2019
DOI: 10.1097/qai.0000000000002003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term HIV Pre-exposure Prophylaxis Adherence After Study Participation in Men Who Have Sex With Men

Abstract: for the California Collaborative Treatment Group (CCTG) 601 Team Background: Efficacy of HIV pre-exposure prophylaxis (PrEP) among men who have sex with men is well documented in randomized trials. After trial completion, participants are challenged with acquiring PrEP on their own and remaining adherent. Methods: This was a follow-up study of the TAPIR randomized controlled multicenter PrEP trial. Participants were contacted after their last TAPIR visit (ie, after study-provided PrEP was discontinued) to atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Thus, HIV screening programs in San Diego specifically have been shown to be successful in both decreasing HIV diagnoses in the area, and terminating transmission chains where the program was marketed 4,6,15 . The low rate of 0.26% new HIV diagnoses that we observed in our ED HIV screening program may therefore be explained by the high density of free-of-charge HIV screening programs, and potentially also by increasing use of HIV pre-exposure prophylaxis in high risk individuals 19–21 .…”
Section: Discussionmentioning
confidence: 85%
“…Thus, HIV screening programs in San Diego specifically have been shown to be successful in both decreasing HIV diagnoses in the area, and terminating transmission chains where the program was marketed 4,6,15 . The low rate of 0.26% new HIV diagnoses that we observed in our ED HIV screening program may therefore be explained by the high density of free-of-charge HIV screening programs, and potentially also by increasing use of HIV pre-exposure prophylaxis in high risk individuals 19–21 .…”
Section: Discussionmentioning
confidence: 85%
“…Some sources report chemsex users as having relatively controlled drug use and maintaining safe sex strategies whilst under the influence of chemsex drugs (Graf, Dichtl, Deimel, Sander & Stover, 2018), or completely compartmentalising chemsex from the rest of their lives (Ahmed et al., 2016), suggesting that daily PrEP adherence around chemsex events can be achievable. A follow-up study of the TAPIR PrEP trial also found “less problematic” substance use to be a significant predictor of adequate adherence (Hoenigl, Hassan et al., 2019) and a recent study among Australian GBM has reported increased concurrent use of methamphetamines, Viagra and Truvada Ⓡ -PrEP, demonstrating how PrEP can be added alongside chemsex drug use to mitigate against HIV risk (Hammoud et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another American GBM study found similar associations with instances of “club drug” use (including GHB and methamphetamine) being correlated with missed PrEP doses on the same day (Grov, Rendina, John, & Parsons, 2018). Conversely, the same research also suggested that on average “club drug” users were no more likely to miss PrEP doses than non “club drugs” users (Grov, Rendina, John, & Parsons, 2018), and in another study among American GBM, methamphetamine use was shown not to be associated with decreased PrEP adherence (Hoenigl et al., 2019, Hoenigl et al, 2019). Interestingly, in an IPERGAY trial substudy, GBM reporting chemsex were more likely to report correct PrEP use during their most recent sexual encounter, which authors have explained by their additional finding that participants reporting chemsex also reported having a higher risk perception (Roux et al., 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Meeting partners over Grindr™ or other geosocial networking apps may also facilitate serostatus disclosure, serosorting, negotiation regarding condom usage, discussion of sexual practices and user risk-assessment, therefore lowering overall risk [6,12,13]. Although Grindr may also serve as a forum to discuss HIV the use of pre-exposure prophylaxis (PrEP) [14] among Grindr™ users remains a under-explored topic [15].…”
Section: Introductionmentioning
confidence: 99%